UJI PENINGKATAN KONSENTRASI Metarhizium anisopliae (Metsch.) PADA MEDIA KOMPOS DALAM MENGENDALIKAN LARVA Oryctes rhinoceros L. - Hafiz Fauzana; Miftahul Fadilla (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The Rhinoceros beetle (Oryctes rhinoceros) is the main pest of palm oil (Elaeis guineensis Jacq.). Biological control using Metarhizium anisopliae fungus was effective in controlling O. rhinoceros. M. anisopliae fungus can be applied on palm oil empty bunches (POEB) which composted (Metankos). The research result in 2019 that a concentration of 50 g.l-1 M. anisopliae only kill 56% of O. rhinoceros larvae, so an increase in application concentration was tested. This research aimed to obtain the best concentration by increasing the concentration of M. anisopliae in POEB compost mixed with sawdust in controlling O. rhinoceros L. larvae. The research was conducted at The Plant Pest Laboratory Faculty of Agriculture University of Riau, to January until April 2021, using a completely randomized design (CRD), consist five treatment and four replications, concentration of M. anisopliae in compost was 55 g.l-1 water, 65 g.l-1 water, 75 g.l-1 water, 85 g.l-1 water, 95 g.l-1 water. The research showed that an increase in the concentration of M. anisopliae in compost of 75 g.l-1 water could be categorized as biopesticides because it caused an total mortality is 72,50 ± 5,00. The lethal concentrations 50% and 95% of M. ansiopliae in compost is 48 g.l-1 water approach to concentration 55 g.l-1 water and 140 g.l-1 water approach to concentration 95 g.l-1 water.